ANALYSIS OF THE EFFECT OF FINANCIAL PERFORMANCE AND MACRO ECONOMIC FACTORS ON THE RETURN OF FOOD & BEVERAGE STOCK COMPANIES IN INDONESIA STOCK EXCHANGE FOR THE PERIOD 2015-2019 - Dilla Syukrina Tascha; Matrodji H. Mustafa (Dinasti Publisher, 2021)
The purpose of this study is to analyze financial performance through Current Ratio (CR), Total Asset Turn Over (TATO), Debt to Equity Ratio (DER), Return on Equity (ROE) and macroeconomic factors through Gross Domestic Product (GDP) to stock returns. The object of research is a food and beverage company on the Indonesia Stock Exchange for the period 2015-2019. The analysis data used are financial reports, stock returns and GDP growth. The research sample of 15 companies obtained by purposive sampling technique. The data analysis technique used is Panel Data Regression Analysis with eviews version 9. The results show that Current Ratio (CR) and Debt to Equity Ratio (DER) have a significant positive effect on stock returns, while Total Asset Turn Over (TATO), Return on Equity (ROE) and Gross Domestic Product (GDP) have no significant effect on stock returns.